Anthracycline Cardiotoxicity: Prevalence, Pathogenesis and Treatment - Volkova, Maria (Bentham Science Publishers, 2011)
Anthracyclines, such as doxorubicin and idarubicin, remain an important class of chemotherapeutic agents. Unfortunately, their efficacy in treating cancer is limited by a cumulative dose-dependent cardiotoxicity, which can cause irreversible heart failure. In this review, we discuss the pathogenesis and incidence of anthracycline-induced cardiotoxicity as well as methods to detect, prevent and treat the condition.